Understanding and combatting terrorist networks: Coupling social media mining with social network analysis - Van Den Ende, Benn (2016)
Throughout the past decade the methods employed by terrorist organisations have changed drastically. One of these key changes has been associated with the rise of social media such as Facebook, Twitter, YouTube and blogging in general. Terrorist organisations appear to be using the wide reach and vast network capabilities created by social media to disseminate propaganda, radicalise susceptible individuals, recruit potential fighters and communicate strategic and operational objectives. However, this growing terrorist presence on Social Media can also offer invaluable insights into the social networks of terrorist organisations through the use of Social Media Mining and Social Network Analysis. By coupling these two techniques together, researchers can gain a greater understanding of how to combat and possibly destabilise complex terrorist social networks and aid in the fight against radicalisation and terrorism